Research advances Progress in mechanistic studies of renal fibrosis based upon regulatory cell death - Sheng Zhong; Jing Tan; Zhi-jun Deng; Jin-rong Wang; Guang-ming Yin; Xian-zhen Jiang (Editorial Department of Journal of Clinical Nephrology, 2024)
As a basic pathological feature at advanced stage of various kidney diseases, renal fibrosis (RF) is an important cause of kidney failure. It is characterized by an excessive accumulation of extracellular matrix (ECM), damage of renal tissue structure and loss of renal function. Regulated cell death (RCD) is closely correlated with RF since it involves a signaling cascade involving effector molecules. This review summarized the mechanism of RCD involved in the progression of RF and provided references for clinical treatment of RF.